2013
DOI: 10.1002/jmv.23492
|View full text |Cite
|
Sign up to set email alerts
|

Clinical symptoms, immune factors, and molecular characteristics of an adult male in Shenzhen, China infected with influenza virus H5N1

Abstract: On December 29, 2011, a man infected with a subclade of the H5N1 virus was confirmed in Shenzhen, China. The clinical symptoms and immune factors of the patient were investigated and the phylogenetic and molecular characteristics of the virus were analyzed. High fever, rapid development of serious pneumonia and multi-organ failure were the main clinical symptoms. Arterial blood gas analysis showed that PaCO2 rose sharply and PO2 decreased. Leukocyte and platelet counts decreased rapidly. Peripheral blood lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
(41 reference statements)
1
8
0
Order By: Relevance
“…5G). Consistent with some human cases previously described [38,39], these results suggested that increases of IL-6 in the serum and lungs might be associated with systemic inflammatory responses leading to death. While increased production of TNFa and IL-1b were also seen in the macaques with severe disease, the other cytokines tested were unlikely correlated with disease severity of the macaques (Figs.…”
Section: Correlation Between Disease Severity and Elevated Levels Of supporting
confidence: 89%
“…5G). Consistent with some human cases previously described [38,39], these results suggested that increases of IL-6 in the serum and lungs might be associated with systemic inflammatory responses leading to death. While increased production of TNFa and IL-1b were also seen in the macaques with severe disease, the other cytokines tested were unlikely correlated with disease severity of the macaques (Figs.…”
Section: Correlation Between Disease Severity and Elevated Levels Of supporting
confidence: 89%
“…The above evidence implies that smoking, drinking, and underlying diseases may be related to the prognosis of H7N9 infection; dyspnea, decreased platelet counts, elevated CK levels, and hypoxemia may be associated with poor prognosis. The time to initiation of antiviral therapy seems to have no impact on prognosis, whereas the presence of complications may be associated with poor prognosis [10]. …”
Section: Discussionmentioning
confidence: 99%
“…Of the 6 patients, 2 emerged from a single family, suggesting that aggregation exists to some extent. In addition, H7N9 avian influenza and H5N1, both of which are fatal, show similar clinical symptoms and disease progression [10,11]. Therefore, early diagnosis and treatment, with an improved cure rate are important to control these infections [11].…”
Section: Introductionmentioning
confidence: 99%
“…H5 replication in humans is mainly supported in alveolar epithelium and alveolar macrophages, which is reflected by the observed clinical signs . Manifestation of human H5N1 infection includes fever, broncho‐interstitial pneumonia, acute respiratory distress syndrome with associated hypoxaemia and multiple organ failure . In the absence of respiratory involvement, infection may also present as a gastrointestinal infection or encephalopathy .…”
Section: Introductionmentioning
confidence: 99%